(untitled) (Research, Society and Development, 2021)
Objective: To investigate the correlation between school dropout indicators in public and private elementary schools and the prevalence of hospitalizations for self-injurious behaviour among children and adolescents aged 5 to 14 years in the state of Paraíba. Methodology: An ecological and exploratory study with time-series design between the years 2009 and 2018, using secondary data collected from the National Institute of Educational Studies and Research Anísio Teixeira (INEP) and the National Notifiable Diseases Information System (SINAN). Statistical analyses of the present study were performed using R (version 3.6.2). Results: A total of 205 hospital admissions for self-injury among schoolchildren and adolescents were reported, with an annual mean of 20.5±20.17. The volume of self-harm increased significantly from the year 2014. In the same period, the average annual school dropout rate was 13.07±4.3. From 2017 onwards, there was an increase in dropout in urban area schools and a decrease in rural schools. Conclusion: It is expected that this study can contribute to the advancement of discussions about the social role of the school as a facilitator of psycho-pedagogical strategies and public policies in mental health focused on coping with social and environmental factors associated with child self-injury and school dropout.